Flexural behaviour of the two-way spanning reinforced concrete slab using spherical plastic bubble balls - Muhamad Khairussaleh, N.A.; Omar, R.; Mat Aris, S.; Mohd Nor, M.F.; Mohd Saidi, M.A.; Nik Mohd Mahari, N.M.A (Institute of Physics, 2023)
The use of conventional reinforced concrete in the construction industry increases each year, especially in developing countries. However, the concrete content, particularly cement production contributed to the greenhouse gas emission subsequently increase to climate change. Thus, the reinforced concrete slab containing high-density polyethene (HDPE) hollow spherical plastic bubble balls also known as bubble deck slabs were introduced for sustainable construction. This type of slab forms a slab that has less concrete volume compared to the normal solid reinforced concrete slab. Although this unique system can facilitate up to a 50% longer span compared to the conventional reinforced concrete solid slab, yet, it can cause the performance of the slab structure such as flexural and shear capacity may be affected due to the thirty to forty per cent of fewer concrete volumes. Hence, this paper studies the comparison of the performance of the two-way supported slabs; reinforced bubble deck slab and normal solid reinforced concrete slab after being subjected to the area loading. The square slabs are 1200mm by 1200mm in width and length with a thickness of 235mm. The investigations of the experiments included flexural strength, bending stiffness and load-deflection behaviour due to the impact of the area loading. Also, the crack propagation and crack pattern which differs also was shown for each type of slab system, especially in shear strength.